Social history of England - Padmaja Ashok (Hyderabad Orient Blackswan, 2022)
The Social History of England is a concise survey of the important historical and political milestones of English history, from pre-history to the present. As a study that examines their impact upon the society and the literature of England, it is both crucial and indispensable for a complete understanding and appreciation of English literature. The book encapsulates more than two thousand five hundred years of history. It includes chapters on the origin and growth of political parties in England and also the impact of major internal and international events on contemporary life in England. The simple and straightforward approach of The Social History of England is supplemented with genealogical charts, maps and a glossary, which are very useful to the student.
Keywords: History of England; Industrial Revolution; Rulers of England; Colonies of the British Empire